High-sensitivity C-reactive protein and all-cause mortality in patients with diabetic foot and osteoporosis: evidence from a retrospective cohort study - Liu, Ting; Xu, Gu-Gen; Chen, Bo; Zeng, Ke-Jing; Weng, Yu; Li, Ping; Xiao, Yi; Liu, Hai-Ming; Fan, Mei-Qiu; Chen, Peng-Cheng (Frontiers in Medicine, 2026)
ObjectiveDiabetic foot (DF), often accompanied by osteoporosis, greatly increases the risk of disability and death. Inflammation is a key driver, with high-sensitivity C-reactive protein (Hs-CRP) serving as a marker of low-grade systemic inflammation. Yet, its prognostic role in this population remains unclear. This study aimed to evaluate the association between Hs-CRP and all-cause mortality in patients with osteoporosis complicated by DF.MethodsThis investigation was a single-center retrospective cohort study that enrolled 468 hospitalized patients with osteoporosis complicated by DF at the Affiliated Guangdong Second Provincial General Hospital of Jinan University between July 2020 and August 2025. Cox proportional hazards models, subgroup and sensitivity analyses were employed to examine the independent association between Hs-CRP and all-cause mortality. In addition, receiver operating characteristic (ROC) curves and restricted cubic spline (RCS) modeling were applied to assess the predictive performance of Hs-CRP and to explore potential dose–response relationships.ResultsDuring a median follow-up of 38.4 months, a total of 50 deaths were recorded. Cox proportional hazards regression demonstrated a significant positive association between Hs-CRP and all-cause mortality. After full adjustment for potential confounders, each 1 mg/L increase in Hs-CRP was associated with a 1.6% higher risk of death (HR = 1.016, 95% CI: 1.004–1.027, p = 0.008), while a one–standard deviation rise corresponded to a 30.7% increase in risk (HR = 1.307, 95% CI: 1.074–1.590, p = 0.008). Patients in the high Hs-CRP group exhibited nearly double the mortality risk compared with those in the low group. Subgroup analyses revealed that this association was particularly evident among individuals aged > 65 years, males, those with hypertension, or those without dyslipidemia. Sensitivity analysis excluding participants with impaired renal function yielded consistent results, supporting the robustness of the findings. The ROC curve indicated that Hs-CRP had moderate discriminatory ability for mortality prediction (AUC = 0.748, 95% CI: 0.686–0.811, p < 0.001). RCS analysis further confirmed a linear dose–response relationship between Hs-CRP and mortality risk (P-nonlinear = 0.910).ConclusionHs-CRP is independently associated with all-cause mortality in patients with osteoporosis complicated by DF, indicating its value for providing a potential tool for risk stratification.